2009
DOI: 10.1002/anie.200806177
|View full text |Cite
|
Sign up to set email alerts
|

Singly Hydrogen Bonded Supramolecular Ligands for Highly Selective Rhodium‐Catalyzed Hydrogenation Reactions

Abstract: H bonds make the catalysts! A single hydrogen bond between ligands coordinated to a rhodium center is critical for the formation of pure supramolecular catalysts for asymmetric hydrogenation reactions. The ester group of the amidite ligand (see scheme) also forms a hydrogen bond with the coordinated substrate. Use of the heterocomplex afforded the highest enantioselectivity reported to date for the hydrogenation of several ester substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 65 publications
2
73
0
Order By: Relevance
“…[8] This complex affords the highest enantioselectivity (> 99 % ee)reported up to now for the hydrogenation of methyl 2-hydroxymethacrylate (and several of its derivatives), which upon hydrogenation forms the so-called "Roche ester", an important intermediate in the preparation of several biologically active compounds.C atalScheme 1. The chemical structures of the ligand building blocks with H-bond acceptors (L1-L4)a nd H-bond donor (L5), and atypical example of aself-assembled bidentatel igands around arhodium complex (6).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…[8] This complex affords the highest enantioselectivity (> 99 % ee)reported up to now for the hydrogenation of methyl 2-hydroxymethacrylate (and several of its derivatives), which upon hydrogenation forms the so-called "Roche ester", an important intermediate in the preparation of several biologically active compounds.C atalScheme 1. The chemical structures of the ligand building blocks with H-bond acceptors (L1-L4)a nd H-bond donor (L5), and atypical example of aself-assembled bidentatel igands around arhodium complex (6).…”
mentioning
confidence: 91%
“…[8] Instead, the OH group inserts in the existing hydrogen bond between L1 and L5,l eading to the formation of two hydrogen bonds between the substrate and the complex (Figure 1). This complex was found to be 5.45 kcal mol À1 more stable than the alternative complexes that were computed, and as such is the major catalystsubstrate species observed in solution.…”
mentioning
confidence: 99%
“…For instance, the elegant systems employed by the group of Jun [94] and Breit et al, [95] wherein the ligand interacts strongly with the substrate of choice -be it an aldehyde to infer selective hydroacylation, through the formation of a reversible imine bond, or the hydroformylation of α,β-unsaturated carboxylic acids, making use of directing H-bonding -have been tested mainly with Rh and Ru. Related approaches using bifunctional substrate activation have been developed by Reek et al, wherein hydrogen bonding interactions [96] between the ligands and the substrates were shown to enhance the asymmetric hydrogenation of functionalized substrates. The use of an anion-binding pocket as the backbone of a diphosphorus ligand was able to regulate the regioselectivity during the rhodium-catalyzed hydroformylation of unsaturated carboxylate substrates.…”
Section: Supramolecular Cooperative Catalysismentioning
confidence: 98%
“…74 Interestingly, Reek and coworkers have also reported the generation of heterodimeric supramolecular complexes by hydrogenbonding-mediated assembly of a phosphoramidite, which is a good hydrogen bond donor, and the urea carbonyl group, in the presence of a rhodium precursor. 75 NMR studies revealed that the heterodimeric complex 62 ( Figure 5) was the only complex that was formed (>99% purity). The authors then assayed the heterodimeric complex 62 in the rhodium-mediated asymmetric hydrogenation of methyl 2-(hydroxymethyl) acrylate (Roche's ester).…”
Section: Use Of Hydrogen Bonding In the Construction Of The Catalyst mentioning
confidence: 99%